Is Serum TGF-β1 and TGF-β2 levels Correlated to Children with Autism Intensity? - yousefi, Jamshid; Khakzad, Mohammad raze; Hojati, Maryam; Ebrahimi, Seyed Ali; Hosseinpour, Mitra; Akhondian, javad (Iranian Journal of Child Neurology, 2021)
Objective Transforming growth factor-beta (TGF-β), a group of multifunctional growth factors, plays an important role in the neuron survival and neurodevelopmental functions. Some studies have evaluated the correlation between TGF-β1 and TGF-β2 abnormalities and autism spectrum disorders. In this study, we compared the TGF-β1 and TGF-β2 levels between autistic and intellectually normal individuals. Materials & Methods The study population consisted of 39 autistic and 30 age-matched intellectually normal individuals (control group). Blood samples were taken from all individuals, and all patients were divided into 2 groups (mild-to-moderate and severe) according to the childhood autism rating scale. The cytokines levels were measured by Enzyme Linked Immunosorbent Assay (ELISA). Results The mean concentration of TGF-β1 was signiﬁcantly lower (P < 0.0001) in children with autism compared to the control group (25.3 ± 6.5 versus 35.1 ± 9.4 ng/mL, respectively). Also, the mean concentration of TGF-β2 in children with autism (32.35± 7.75 ng/mL) was higher compared to those in the control group (30.47± 4.36 ng/mL); however, this difference did not reach statistical significance (P = 0.21). A positive correlation was observed between TGF-β1 concentration and autism severity (r = 0.41; P = 0.02), whereas a negative correlation was found between TGF-β2 concentration andautism severity (r = -0.41; P = 0.02). Conclusion The results of the present investigation suggest that there is a decrease in the levels of TGF-β1 in the serum of patients with autism and this cytokine may be effective in the treatment of the pathophysiological aspects of autism.